Impaired mitochondrial fatty acid oxidation and insulin resistance in aging: novel protective role of glutathione. Issue 3 (19th April 2013) - Nguyen, Dan; Samson, Susan L.; Reddy, Vasumathi T.; Gonzalez, Erica V.; Sekhar, Rajagopal V.
Summary Aging is associated with impaired fasted oxidation of nonesterified fatty acids (NEFA) suggesting a mitochondrial defect. Aging is also associated with deficiency of glutathione (GSH), an important mitochondrial antioxidant, and with insulin resistance. This study tested whether GSH deficiency in aging contributes to impaired mitochondrial NEFA oxidation and insulin resistance, and whether GSH restoration reverses these defects. Three studies were conducted: (i) in 82‐week‐old C57BL/6 mice, the effect of naturally occurring GSH deficiency and its restoration on mitochondrial 13C1‐palmitate oxidation and glucose metabolism was compared with 22‐week‐old C57BL/6 mice; (ii) in 20‐week C57BL/6 mice, the effect of GSH depletion on mitochondrial oxidation of 13C1‐palmitate and glucose metabolism was studied; (iii) the effect of GSH deficiency and its restoration on fasted NEFA oxidation and insulin resistance was studied in GSH‐deficient elderly humans, and compared with GSH‐replete young humans. Chronic GSH deficiency in old mice and elderly humans was associated with decreased fasted mitochondrial NEFA oxidation and insulin resistance, and these defects were reversed with GSH restoration. Acute depletion of GSH in young mice resulted in lower mitochondrial NEFA oxidation, but did not alter glucose metabolism. These data suggest that GSH is a novel regulator of mitochondrial NEFA oxidation and insulin resistance in aging. Chronic GSH deficiency promotes impaired NEFA oxidation and insulin resistance, and GSH restoration reverses these defects. Supplementing diets of elderly humans with cysteine and glycine to correct GSH deficiency could provide significant metabolic benefits.